NHLRC1 dodecamer repeat expansion demonstrated by whole genome sequencing in a Chihuahua with Lafora disease - Barrientos, Laura Soledad (2018)
Lafora disease is an autosomal recessive disor-der that causes myoclonic epilepsy.The disease is char-acterized by the presence of polyglucosan inclusion bodies (Lafora bodies), predominantly in the central nervous sys-tem. More than 90% of human Lafora disease cases arecaused by genetic variants in eitherEPM2A, encodinglaforin glucan phosphatase, orNHLRC1,encoding the NHLrepeat containing E3 ubiquitin protein ligase 1, also termedEPM2B or malin. Lafora disease in animals has similarclinical signs as the human disease, including spontaneousand reflex myoclonus, jerks and generalized tonic clonic sei-zures. Lafora disease has been reported in the dog, cat, cow and fennec fox.In dogs, Lafora disease is one of themost commonly recognized structural-metabolic epilepsiesand is inherited as an autosomal recessive condition. It ismost frequent in Miniature Wirehaired Dachshunds, BassetHounds and Beagles and has also been reported in theMiniature and Standard Poodle, Pointer and Corgi. Asingle disease-causing variant has been found in dogs. It consists of a massive expansion of a GC-rich dodecamerrepeat sequence in the canineNHLRC1gene, leading to lossof function of the gene. The wild type allele of this repeatconsists of two copies of a 12-bp motif in most mammalianspecies. In normal dogs and other canids two or threecopies are present. The pathogenic alleles leading to Laforadisease in dogs were reported to contain 14-26 copies ofthis repeat.2Genetic testing and carrier detection are notroutinely available, as the extremely GC-rich dodecamerrepeat expansion impedes PCR-based diagnostic approaches.Currently, a Southern-blot-based test is offered by theHospital for Sick Children in Toronto and represents an offi-cial DNA screening test recommended by the UK KennelClub.